Land Acquisition in the Job Creation Law in the Perspective of Islamic Ownership Theory (an Analysis with the Concept of Istimlak and Milk al-daulah) - Husnul Mirzal; Muhammad Wicaksono Hasdyani Putra; Shally Nur Rasyida (Ijtihad, 2021)
The Job Creation Law is one of the priority program proposed by the executive to the legislature. Since it was proposed by the executive to be discussed by the legislature, this law has generated protests from some people because some of the articles in it are considered controversial, including the chapter on land acquisition. This study wanted to look at some of the provisions of the Land Acquisition chapter in Job Creation Law in the perspective of istimlak and milk al-Daulah. The study used a qualitative method with a normative-juridical analysis approach to the library data sources. The results of this study indicate that there are several problems in the chapter of land acquisition in the Job Creation Law in terms of the concept of Istimlak and milk al-daulah, namely the addition of letters regarding the criteria of public interest and in the elimination of analysis of environmental impacts on land objects of acquisition. The addition of the criteria for land to be the object of acquisition contradicts the concept of Istimlak because the intended use of the land to be acquired does not meet dharuriyah criteria, while the elimination of obligations for environmental impacts analysis is contrary to milk al-daulah because it can cause harm to humans and the universe.